One-step preparation of carboxymethyl cellulose/polyoxyethylene nanofiber mats containing silver nanoparticles. Issue 169 (12th February 2016) - Wang, Feijun; Shi, Dandan; Lan, Tian; Zhang, Yunhua; Shao, Ziqiang
ABSTRACT: This paper addresses a simple method to prepare antibacterial carboxymethyl cellulose (CMC)/polyoxyethylene(PEO) nanofiber mats containing silver nanoparticles (Ag NPs). The nanofibers are fabricated by electrospinning of CMC/PEO/AgNO3 blend aqueous solution with an AgNO3 concentration of 10mmol/L. In electrospinning procedure, Ag NPs with average diameter of 4.5 nm are obtained and separated from each other on the surface of CMC/PEO nanofibers. The nanofibers have smooth surface and narrow size distribution. The CMC/PEO/Ag NPs nanofiber mats show good antimicrobial activity against E . coli and photoluminescent performance, which can be applied in biomedicine such as wound dressings or anti-adhesion membranes.